Strength and permeability of ferrocement structure by using ground granulated blast furnace slag - Purwaningsih, Anis; Dewi, Sri Murni; Susanti, Lilya (Universitas Mercu Buana, 2024)
A reinforced mortar type that can be created with a relatively thin thickness is ferrocement. Using ferrocement as a mechanically sound and sustainable building material has produced several benefits, including less use of raw materials, decreased accumulation of waste materials, and reduced greenhouse gas emissions. Cement as a constituent material of ferrocement is an environmentally unfriendly material; therefore, a more environmentally friendly cement replacement material is needed, namely Ground Granulated Blast Furnace Slag (GGBFS). Thus, creating sustainable (green) fertilizers is the main goal of this work. There are three primary stages to experimental work: Using slag cement (GGBFS) in place of partial cement of 0%, 10%, 20%, and 30% is the initial step. The primary reinforcement in the second level is wire-welded mesh, with volume fractions of support (Vf) of 1.2%, 1.8%, and 2.4%. During the final phase, a maximum of three different test objects were tested for compressive strength, water penetration depth, and flexure at a 28-day age. According to the findings, employing GGBFS led to good mortar performance. According to studies on mortar, the percentage of GGBFS utilized in a work may be determined by comparing the GGBFS substitution rates of 10%, 20%, and 30%, which show no differences in tendency. The test findings did not considerably improve the bending strength and cracking behavior of ferrocement reinforced with wire-welded mesh. One of them is influenced by the age of the concrete; at 28 days, the added material GGBFS has not yet reached its maximum strength, which results in a negligible improvement in bending strength and cracking behavior.